MAINTENANCE AND REPAIRS SYSTEM OF AUTOMOTIVE INDUSTRY FOR SUSTAINABLE INTERNATIONALIZATION - Ahmadian, Sahar; Alabdullah, Tariq Tawfeeq Yousif; Motaghian, Iraj (Transpublika Publisher, 2023)
The current article investigates the maintenance and repair system within Iran's automotive industry in the context of internationalization and proposes a prioritization model. This study employs the Gogus & Boucher and Chang extent analysis methods to calculate suitability percentages and significant weights, based on a sample of 17 experts from Bahaman Car Manufacturing Co. The proposed model comprises three levels: 1) factors influencing system internationalization; 2) indicators related to cost, speed, capability, and mission compatibility; and 3) sub-criteria for each indicator. The adoption capability holds the highest weight (0.639), followed by implementation speed (0.612), alignment with the organization's mission (0.454), and implementation cost (0.454). Notably, the primary contributors to cost are confidence and supplier competence, while employee competency and responsiveness play crucial roles in speed. The study highlights flexibility as a key competency, with mission compatibility predominantly influenced by IT infrastructure and self-control MR. This research contributes fresh insights to the understanding of effective global growth strategies by shedding light on enhancing the readiness of the maintenance and repair system for internationalization within Iran's automotive industry.